Extreme Wave and Abrasion Disaster Risk Mapping on the Coast of Jembrana Regency, Bali - I Wayan Krisna Eka Putra; Si Ngurah Ardhya; Gusti Ngurah Putu Pungky Subawa; I Putu Juli Wirawan; Ni Putu Ega Kemalayanti (Universitas Pendidikan Ganesha, 2026)
This study aims to map the risk level of extreme waves and abrasion disasters in the coastal areas of Jembrana Regency, Bali. The method used includes hazard, vulnerability, and capacity mapping using a GIS-based spatial approach. The analysis was conducted using an overlay technique of three main components: the hazard index, the vulnerability index, and the capacity index to generate a disaster risk index. Data were obtained from secondary sources such as the National Disaster Management Agency (BNPB) and previous studies, and processed using weighting. The results show that most of the coastal areas of Jembrana, especially Pekutatan, Mendoyo, and Jembrana Districts, are categorized as high risk, while Negara and Melaya are categorized as medium. The area with high hazard reaches 7.16 km². This condition indicates the need to strengthen coastal spatial planning-based mitigation and adaptation strategies to reduce the impact of future disasters as part of the disaster management process.